SOCIAL INTEGRATION OF SYSTEM COMPONENTS OF THE ORGANIZATION AS ONE OF THE OBJECTIVES OF THE MANAGEMENT ACTIVITY - S. Frolov (Вестник университета)
The problem of the creation and development of social integration affects virtually every part of the vital activity of a modern society. The challenge of integrating a special place occupies in the management of social organizations. To achieve a high level of social integration allows an organization to solve many problems of their own activities, establish links with the external environment, to create viable and sustainable.